Utilization of Science and Technology for the Community: E-stock Inventory Manager at Cracker Producers in Kampung Kerupuk, Tambak Bulak Hamlet, Sidoarjo Regency - Fauzatul Laily Nisa; Muhammad Ahmi Husein; Putra Perdana (Nusantara Science and Technology Proceedings, 2022)
Kampung Kerupuk has the advantage of being close to Surabaya, the logistics backbone in Indonesia. with logistical advantage in the middle of two big cities, shipping, and forwarding can be done quickly and efficiently. Although they have a logistical advantage, producers are still not able to maximize this advantage to increase their production and sales. One of the inhibiting factors is that the management of stocktaking is still traditional and conservative so the record and management of inventory are limited. The policy concept designed to address this problem is to introduce manufacturers to the digitization of records and connected storage systems. By using stock inventory management, manufacturers can efficiently record with more precision and real-time. From the programs that have been implemented, it is found that, although almost all producers object to adopting this digitalization after being given socialization, almost all producers will use this stock inventory continuously. Some producers who are reluctant to adopt the system are constrained by technical problems and do not necessarily eliminate the intention to use the system in the future.